2008
DOI: 10.1007/s11224-008-9329-4
|View full text |Cite
|
Sign up to set email alerts
|

Structures and thermodynamic properties of aluminum oxyhalides: a computational study

Abstract: The molecular geometries and vibrational frequencies of aluminum oxyhalides, AlOX, and their dimers, (AlOX) 2 , have been calculated by MP2 and density functional methods. The monomeric molecules are linear while the dimers have a D 2h -symmetry geometry with a fourmembered ring, in which the oxygen atoms serve as bridging ligands. Different thermodynamic properties have been calculated; for AlOBr and AlOI for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The validity of the few available experimental data for Al x O y Cl z species is also rather questionable. Varga et al 16 suggest the JANAF value ∆ f H 298.15K °) -348.11 kJ/mol for AlOCl (g) may require review; they cite a value of -280.3 kJ/ mol from experiment. Table 2 also shows the considerable discrepancy between values reported in JANAF and the CRC Handbook 28 for less observable aluminum species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The validity of the few available experimental data for Al x O y Cl z species is also rather questionable. Varga et al 16 suggest the JANAF value ∆ f H 298.15K °) -348.11 kJ/mol for AlOCl (g) may require review; they cite a value of -280.3 kJ/ mol from experiment. Table 2 also shows the considerable discrepancy between values reported in JANAF and the CRC Handbook 28 for less observable aluminum species.…”
Section: Resultsmentioning
confidence: 99%
“…A small number of TiAl x Cl y species have been studied experimentally, , but the system with excess oxygen has not been investigated. Varga et al provide thermochemical data for some of the aluminum oxyhalides from computational studies but a number of possible species, particularly dimers, are missing. It is also possible that the impact of AlCl 3 is entirely physical in which case it would be useful to rule out any significant chemical interaction.…”
Section: Introductionmentioning
confidence: 99%
“…While the increase in the R ct value, which was observed for the first 3 h, was attributed to the passive film developed on the surface, the decrease observed in the R ct value afterward was attributed to the degradation of this passive film [27]. This study also revealed the importance of evaluating corrosion, which is a dynamic process, at the end of a longer time period, in contrast to performing electrochemical measurements after 1 or 2 h. The R ct measurements of the AA6060 alloy obtained after 50 s in the DEIS experiment and those obtained at the end of 48 h are parallel to the results of a previous study [17].…”
Section: Tablementioning
confidence: 91%